Analysis of the Performance of the Students from the State Exam in the “Accounting” Bachelor Major for the Period 2017 – 2021 and Major “Accounting and Control” (Distance Learning) for the Period 2020/2021 - Bachev, Iavor (Research Papers, 2022)
The article presents the results and conclusions from the analysis of the results from the state exam in the “Accounting”, Bachelor’s degree, for a period of five years (2017 – 2021) and distance learning students for the academic year 2020/2021. The object of research are the state exams of the students in the bachelor major “Accounting” held in July 2017, 2018 and 2021 and the state exam of the students in the major “Accounting and Control“ held in July 2021.The subject of this article is focused on the analysis of the overall success by modules of students and in particular of the module “Financial Accounting” in general, by groups of questions contained in the module and specific questions in each group of the module “Financial Accounting”. The discipline “Financial Accounting” is one of the fundamental disciplines and together with the “General Theory of Accounting” and plays the most important role in the formation of basic theoretical knowledge and practical skills in students. It is included in the range of disciplines required to obtain a certified public accountant. qualification.The aim of the research is to outline the modules in which the most problematic issues arise; to bring out the topics and the nature of the questions from the module “Financial Accounting”, which are most difficult for students and to formulate the factors that have influenced the success of students and to make specific recommendations for improving the organization of the state exam.